TYPES ACCORDING TO THE STRUCTURE OF THE SENTENCE - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article describes the types of sentences according to the structure of the studied language, sentence formation and structures, and other word groups used in the sentence.